Medical emergency and healthcare model: enhancemet with SMS and MMS facilities - Hameed, Shihab A.; Miho, Vladimir; Mohammed Al-Khateeb, Wajdi Fawzi; Hassan Abdalla Hashim, Aisha (2010)
The study of the current Malaysian emergency,healthcare and medical information systems shows that they have several drawbacks such as lack of sharing between hospitals, no integration between emergency, healthcare and medical information systems, lack of utilizing real-time and mobility technologies, and stand alone systems. Thus, this paper is to develop a system that integrates medical emergency, healthcare and medical information systems together in order to overcome many of the above problems. The main focus of this work is to incorporate the real-time and mobility technologies with medical emergency systems. It can offer: SMS, MMS, live audio and video coverage of emergency situations, location-based access to emergency situation, wide area coverage, and provides flexibility for the user. A prototype for the model is implemented using open source tools. Samples of implementation results are shown. This project is an essential as it will be the first model in Malaysia that integrates healthcare, medical and emergency systems.